Écrire au réconfort de Dieu. La patrimonialisation des savoirs administratifs des monarchies marocaine et tunisienne sous le Protectorat - Antoine Perrier (L’Année du Maghreb)
The Tunisian and Moroccan Protectorates have submitted the Sherifian and Beylical monarchies to a process of “patrimonalization”. French authorities have consequently selected few administrative methods and institutions among State patrimonies to maintain them under the colonial rule. This strategy let political tools to Muslim Sovereigns and their servants to resist the French domination. Through two case studies (Sultan’s dahirs of appointment and Beys court) based on Arabic sources, this paper shows how Sovereigns and servants reinvented this patrimony and why resistance against colonial order was neither only a question of “modernity” vs. “tradition”, nor the monopoly of nationalist parties.